Immunological predictors in children with hypoxic-ischemic encephalopathy - E. S. Kuzmina; L. Yu. Barycheva; O. V. Agranovich; A. S. Idrisova (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
.